DOI: 10.31274/etd-180810-1334
|View full text |Cite
|
Sign up to set email alerts
|

Status, distribution, and habitat associations of Topeka Shiners in west-central Iowa

Abstract: Quist for their guidance and instruction. Their expertise in scientific research, writing, and communication was invaluable to this project and to my growth as a student and fisheries professional. Much thanks also to Dr. Philip Dixon, who served on my committee and provided valuable insight. This project would not have been possible without the faculty, staff, and students of Iowa State University, the Department of Natural Resources, and the Iowa Cooperative Fish and Wildlife Research Unit. I would like to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Both species are associated with instream habitat dominated by slow current and vegetated backwaters (Carl, Clemens, & Lindsey, ; Nelson & Paetz, ; Page & Burr, ; Pflieger, ). Bakevich () often found lentic species, including brassy minnow and Topeka shiner, together in oxbows and suggested that the two species are able to persist in harsh conditions that are common to oxbows throughout the year. In areas of Iowa and Minnesota with altered streams, it is possible that, with a decline in preferred instream habitats, Topeka shiners and brassy minnows both seek out oxbows as a substitute for instream pools and backwaters.…”
Section: Discussionmentioning
confidence: 99%
“…Both species are associated with instream habitat dominated by slow current and vegetated backwaters (Carl, Clemens, & Lindsey, ; Nelson & Paetz, ; Page & Burr, ; Pflieger, ). Bakevich () often found lentic species, including brassy minnow and Topeka shiner, together in oxbows and suggested that the two species are able to persist in harsh conditions that are common to oxbows throughout the year. In areas of Iowa and Minnesota with altered streams, it is possible that, with a decline in preferred instream habitats, Topeka shiners and brassy minnows both seek out oxbows as a substitute for instream pools and backwaters.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported that Topeka shiners prefer more turbid waters, but this was assigned to possible increased sampling efficiency (Simpson et al, 2019). Water depth was found to have no (Simpson et al, 2019) or mixed influences on Topeka shiner occurrence, but there was an overall preference for shallower oxbows (Ceas and Larson, 2010;Bakevich, 2012;Fischer et al, 2018). Simpson et al (2019) found that the presence of woody riparian vegetation was negatively correlated to the Topeka shiner presence (Simpson et al, 2019), while non-woody vegetation had a positive impact on occurrence (Bayless et al, 2003;Simpson et al, 2019).…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…Since the time of listing, studies in the six states have increased knowledge of Topeka shiner distribution, habitat preferences, and environmental relationships, but significant concerns remain for the long-term conservation of the species (USFWS, 2009). Topeka shiners are nearly always found in very low abundance (Lee et al, 1980;Loan-Wilsey et al, 2005;USFWS, 2009), although infrequent large collections (in the 100s) have been reported in South Dakota (USFWS, 2009), Minnesota (Ceas and Larson, 2010), and Iowa (Bakevich, 2012;A. Kenney, USFWS, pers comm.).…”
Section: Introductionmentioning
confidence: 99%